Identifikasi Candida albicans pada Wanita Dewasa di Kota Kendari secara Makroskopis dan Mikroskopis - Hartati Hartati; Maliftha Dwi Aini; Yuliyanti Yasin (Halu Oleo University, 2019)
ABSTRACTBackground: Candida albicans is a major cause of invasive fungal infections and the common health problems that occur in the community. It was reported that 85-90% of C. albicans is a major cause of candidiasis vulvovaginalis (CVV) infections worldwide. Reports from the University of Manchester in England and Wayne State University in the United States of America specified that the prevalence of CVV cases in Indonesia is ranked fourth in the world with 4 million cases. Research Purposes: This research aims to determine the macroscopic and microscopic depiction of C. albicans from vaginal swab in Kendari City. Research Methods: The present research is a descriptive study conducted in adult women who visit the Clinical Laboratory Maxima Kendari to do pap smear of both with and without complaints. The total sampling technique was used for collecting 36 samples. The variables being studied consist of independent variables by macroscopically and microscopically and C. albicans is the dependent variable. Research Result The results showed that as of 36 samples of the secret vaginal, 4 samples (11.1%) were identified positive Candida sp. on direct examination with 10% KOH, 15 samples (41.7%) were positive Candida sp. resulting from gram stain test and culture of sabouraud dextrose agar, and there were 12 samples (80%) detected as positive C. albicans on biochemistry test. Conclusion: Research concluded that C. albicans can be identified by both macroscopic and microscopic analysis. As of 36 secret vaginal samples, 6 samples with complaint and 9 samples without complaint positive contain C. albicans, yet 14 samples with complaint and 7 samples without complaint do not detected C. albicans. Keywords : Candida albicans, swab vagina, macroscopic, microscopic